Geographical Dimensions of the Development in Central Himalayas: A Case Study of Chamoli: Geographical Dimensions, Disasters, and Sustainable Development in the Central Himalayas (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The Chamoli district and other areas of Uttarakhand continues in a very short time to face many disasters, such as landslides and flash floods. Strong rainfall and low shear strength from the rocks made these slides possible. In addition, floods, loose sediments, slopes and river banks were excavated. The main factor triggering and affecting growth are tectonic activities. Many participating in these activities continue to look for their essential needs to survive and restore their lives. Other factors influencing the growth of the region are climate warming and the river systems. Dynamics of the natural vegetation depend on the presence because of the sunlight. The altitude and the pitch are significant obstacles to the exploitation of resources and human operation. These are hurdles to all types of Chamoli district growth, such as roads etc. Different opportunities for sustainable management of water resources with problems for sustainable living of local communities have been discussed for the Garhwal region of the central Himalayan based on a detailed study of traditional ecological information connected with biodiversity, environmental and civilized management. The inference is that if local peoples' development needs are ignored for a long time, they will take action that is counterproductive to the conservation target. The complicated process of ensuring people 's engagement in environmental protection along with the social and economic growth of local communities, by capitalizing on the negative dimension of presenting information and eliminating its negative aspects through traditional scientific inputs.